The amended role of the public prosecutor to resolve with an accused person in expediting the disposal of case - Kamarudin, Abdul Rani; Mohd. Dahlan, Nuarrual Hilal (2011)
The Public Prosecutor makes the final decision whether an offender should be charged with an offence. Article 145(3) of the Malaysian Federal Constitution states clearly stipulates that the Attorney General has the power to institute, conduct or discontinue any proceedings for an offence in any court other than the Syariah Court, Native Court and the Court-Martial. Section 376(1) and (2) of the Malaysian Criminal Procedure Code (hereinafter referred to as the CPC) clarify by stating that the Attorney General, who will be the Public Prosecutor, will have the control and direction of all criminal prosecutions and proceedings under the Code. It is plain and clear from decided cases that the Public Prosecutor determines if any person is to be prosecuted of any offence. It is only right to charge a suspect when the evidence from the police investigation discloses a prima facie case. At the close of the defence which may also be said to be the conclusion of the trial, the prosecution bears legal burden to prove beyond all reasonable doubt that the accused did the offence, or the charge is not proven. This criminal standard of proof required of the prosecution to prove their case beyond all reasonable doubt against the accused is not without hurdles, and can be very time consuming. Accordingly, it makes sense for the prosecution to secure a conviction on a reduced charge by mediating with the accused to plead guilty on a lesser offence, and upon the accused doing so, to withdraw the charge against the accused for the serious offence (felony). In 2010, an amendment was made to the CPC vide the Criminal Procedure Code (Amendment) Act 2010 with its objects among others to address problems of backlog of cases in the criminal courts and towards encouraging the expeditious disposal of criminal cases. The amendment provides that the Public prosecutor need to indulge in pretrial conference, case management and plea bargaining with the accused. This paper thus looks at these amendments and how they have affected the Public Prosecutor from a reactive to proactive role in resolving with an accused person to expedite the disposal of case in accordance with both human rights and humanitarian laws.